FEASIBILITY STUDY FOR THE IMPLEMENTATION OF A DAIRYPRODUCTION SYSTEM ON 10 HECTARES IN THE MATA REDONDASECTOR IN THE PROVINCE OF CARCHI - Rivera Chamorro, Amilcar Alexis; Urgilés Urgilés, Gladys Primavera (Tierra Infinita, 2023)
Dairy production systems play a fundamental role in the agricultural industry. These systems not only focus on the production of dairy products, but also address critical issues related to environmental sustainability and economic stability. This study focuses on evaluating the viability of a self-sustainable dairy production system in the Mata Redonda sector of the province of Carchi. Surveys, interviews and statistical analyses were used, and the population studied is located in the rural municipality of Chitán de Navarretes. The results show that self sustainable dairy production systems can effectively address the environmental, social and economic challenges associated with traditional dairy production. They also promote fair labor practices and contribute to local economic development. The 5-year financial analysis showed encouraging results. Using a discount rate of 5%, the Net Present Value (NPV) is estimated to be 8,311.27, representing the profit after initial investment and financing costs. The Internal Rate of Return (IRR) of 10.2% indicates that the project will break even and start generating profits in 3 years. The Return on Investment (ROI) of approximately 22.45% indicates a potentially profitable investment. In summary, this study highlights the feasibility of implementing a selfsustainable dairy production system in the Carchi region. The results support the adoption of more sustainable approaches in the dairy industry and provide practical guidance to promote sustainable dairy production.